Hematological toxicities of immune checkpoint inhibitors and the impact of blood transfusion and its microbiome on therapeutic efficacy and recipient's safety and survival outcome:A systematic narrative appraisal of where we are now!. (April 2023) - Shouman, Mohamed; Goubran, Hadi; Seghatchian, Jerard; Burnouf, Thierry
Abstract: Classically, patients with solid and hematologic malignancies have been treated with a combination of chemotherapy with or without a holistic targeted strategy using approved conventional therapy. While the evidence-based use of Immunomodulatory drugs and Immune checkpoint inhibitors (ICIs), including those targeting the PD-1, PD-L1 and CTLA-4, have reshaped the treatment paradigm for many malignant tumors and significantly stretched the life expectancy of patients, as for any interventional therapy, the rise in ICI applications, was associated with the observation of more immune-related hematological adverse events. Many of these patients require transfusion support during their treatment in line with precision transfusion. It has been presumed that transfusion-related immunomodulation (TRIM) and the microbiome can pose immunosuppressive effects on the recipients. Looking to the past and beyond and translating available data into practice in the evolving role of pharmaceutical therapy to ICI-receiving patients, we performed a narrative review of the literature on the immune-related hematological adverse events of ICIs, immunosuppressive mechanisms linked to blood product transfusions, as well as the detrimental impact of transfusions and its related microbiome on the sustained efficacy of ICIs and the patients' survival outcomes. Recent reports are pointing to the negative impact of transfusion on ICI response. Studies have concluded that packed RBC [PRBC] transfusions lead to an inferior progression-free and overall survival in patients with advanced cancer receiving ICIs, even after adjustments for other prognostic variables. The attenuation of the effectiveness of immunotherapy likely results from the immunosuppressive effects of PRBC transfusions. It is, therefore, wise to look retrospectively and prospectively at the impact of transfusion on ICI effects and adopt, in the interim, a restrictive transfusion strategy, if applicable, for those patients.